Voicing Philippines and Indonesian Students' Needs of Automated Written Corrective Feedback in EFL Writing Classrooms - Herda, Rozanah Katrina; Principe, Regine Aguilar; Travero, Arnel S.; Pratama Harahap, Muhammad Fadhly; Viantika, Salma; Hamidi, Mohammad Arif (Journal of Education, Language Innovation, and Applied Linguistics, 2024)
In EFL writing classrooms, students learning L2 need correction or feedback for their writing. However, the teachers' limitation in time management becomes one of the reasons students can not gain detailed feedback. In line with that, the growth of the digital platform in the 21st-century learning era brings a thought that corrective feedback for L2 writing can be accessed and gained through automated written corrective feedback (AWCF) to ease students' learning and improve their writing ability. This quantitative study aimed at revealing students' need for automated written corrective feedback. The participants of this study were 532 students from the Philippines and Indonesia. The questionnaire was used to collect data and analyzed using the SPSS version 25 to know the percentage and descriptive statistics. The study's findings revealed that students from two states need technology tools to provide written corrective feedback to improve their writing proficiency in the L2 context while solving their problems of vocabulary and grammar limitations. Furthermore, the feedback can grow their confidence to provide L2 writing. The findings of the student's needs can be used as the basis for creating ideal writing scenarios.